Greyhound tales from Route 66 - Suttle, Howard; Wild Life Unlimited Foundation (Raton, New Mexico Coda Publications, 1993)
Howard Suttle tells 89 wonderful stories about his many motor-coach passengers who managed to travel in all directions at once. They made his years of driving the Mother Road a unique source of amazing
"Cat. No. 0400"--Cassette label.
Don Meyer.
VHS.
83401
Keywords: Bus drivers -- New Mexico; Bus passengers -- New Mexico